Nexus between Consumption, Income and Price Changes: Asymmetric Evidence from NARDL Mode - Raheel Gohar; Bisharat Hussain Chang; Omer Faruk Derindag; Zahida Abro (ETIKONOMI, 2022)
Previous research has primarily examined the link between price, income, and consumer spending using linear regression models. On the other hand, the latest evidence shows an asymmetric link among economic and financial variables. We contribute to the literature by employing a novel technique known as the asymmetric ARDL model. This approach is used to investigate the impact of favorable and unfavorable changes in income and prices on household consumption. The results show that higher income has a substantial and beneficial effect on household expenditures in the short term and long term. On the other hand, a fall in income has no impact on consumer spending. Moreover, for most developing countries, price adjustments have a negligible effect on consumer expenditures. Our findings suggest that implementing the same policy initiatives across periods of rising and falling income and prices may result in potential losses.JEL Classification: E31, F31, C22